Chest drainage systems in use - Zisis, Charalambos (Ann Transl Med, 2015)
A chest tube is a flexible plastic tube that is inserted through the chest wall and into the pleural space or mediastinum. It is used to remove air in the case of pneumothorax or fluid such as in the case of pleural effusion, blood, chyle, or pus when empyema occurs from the intrathoracic space. It is also known as a Bülau drain or an intercostal catheter. Insertion of chest tubes is widely performed by radiologists, pulmonary physicians and thoracic surgeons. Large catheters or small catheters are used based on each situation that the medical doctor encounters. In the current review we will focus on the chest drain systems that are in use.